Correlation of Earlobe Crease and Clinically Identified Forehead Wrinkles with Severity of Coronary Artery Lesions in Patients with Stable Angina Pectoris - Agnes L. Panda; Janry A. Pangemanan; Fanny D. Kojansow (e-CliniC, 2022)
Abstract: Identification of high-risk subjects is crucial in prevention of coronary heart disease. Ear lobe crease and forehead wrinkles are easily identifiable physical signs that could potentially be an indicator of coronary artery lesion severity. This study aimed to determine the relationship between earlobe crease and forehead wrinkles morphology with severity of coronary artery stenosis in patients with stable angina pectoris using modified Gensini score. This was an observational study with a cross-sectional approach. All subjects who met the inclusion criteria were taken photos of their forehead area and both right and left ears. Assessment of scores and correlation analysis of earlobe crease and forehead wrinkles assessment with the severity of coronary artery stenosis using Gensini modification scores were later done. The results showed that from a total of 40 study subjects, 28 patients (70%) were male. Forehead wrinkle scores in patients with stable angina pectoris were mainly classified into score 1 and 2, totalling 32 (80%) patients. Earlobe crease form were dominated by type A (65% vs 35%). Patients with type B morphology on average have a Gensini value of 9 points lower than type A (reference) (p <0.001). As for the Gensini modified score in patients with non-zero forehead wrinkle scores, it was clearly 4âˆ’5 units greater than those with a zero score. However, the sample size of patients with zero forehead wrinkle score was indeed too small (n=3) to make the difference meaningful (p=0.507). In conclusion, there is a significant positive relationship between identification of earlobe crease and the severity of coronary artery stenosis but there is no strong relationship between the identification of forehead wrinkles and the severity of coronary artery stenosis in patients with stable angina pectoris, in this case with a modified Gensini score.Keywords: stable angina; earlobe crease; forehead wrinkles; modified Gensini score